Enhancing the nutritional value of sweet pepper through sustainable fertilization management - Stoleru, Vasile; Mangalagiu, Ionel; Amăriucăi-Mantu, Dorina; Teliban, Gabriel-Ciprian; Cojocaru, Alexandru; Rusu, Oana-Raluca; Burducea, Marian; Mihalache, Gabriela; Rosca, Mihaela; Caruso, Gianluca; Sekara, Agnieszka; Jităreanu, Gerard (Frontiers in Nutrition, 2023)
Introduction The need for healthy foods has become a major concern in our modern world, as the global population continues to grow and environmental challenges intensify. In response to these challenges, researchers have started to explore a range of sustainable solutions, including organic farming practices, precision agriculture, and the development and testing of innovative biofertilizers. Consistent with these ideas come the aim of this study, which sets out to give new insights into the cultivation of two sweet pepper cultivars with economic and nutritional importance in Romania. Methods Two sweet pepper cultivars (Blancina and Brillant), chemically (Nutrifine®), organically (Orgevit®) and biologically (Micoseed®) fertilized were cultivated over the course of two years (2019 and 2020), between April and October, in high-tunnel, by following a split-plot design with three replications. Production parameters (number of fruits, fruit weight, yield), proximate composition (water content, dry matter, total soluble solids, acidity, ash), the content of phytonutrients (polyphenols, lycopene, β-carotene, antioxidant activity), phytochemical composition (phenolic compounds) and minerals (macro- and micro-elements) were analyzed in order to determine the impact of fertilization on the quality of sweet peppers. Results The results showed that the biological and organic fertilizations had a significant positive impact on most of the parameters analyzed, starting with yield and continuing with acidity, phytonutrient content (total phenolic content, lycopene, β-carotene), antioxidant activity and phytochemical composition (chlorogenic acid, p-coumaric acid, quercetin and isoquercetin). Only in the case of mineral content, the chemical treatment gave better results compared with the organic and biological fertilizers. Conclusion Overall, this study provides valuable information on the potential of organic and biological fertilizers to enhance the nutritional value of sweet peppers from Blancina F1 and Brillant F1 cultivars, paving the way for subsequent research aimed at achieving superior quality and increased yields.